Deposition of topological silicene, germanene and stanene on graphene-covered SiC substrates. Issue 1 (December 2017) - Matusalem, Filipe; Koda, Daniel; Bechstedt, Friedhelm; Marques, Marcelo; Teles, Lara
Abstract Growth of X-enes, such as silicene, germanene and stanene, requires passivated substrates to ensure the survival of their exotic properties. Using first-principles methods, we study as-grown graphene on polar SiC surfaces as suitable substrates. Trilayer combinations with coincidence lattices with large hexagonal unit cells allow for strain-free group-IV monolayers. In contrast to the Si-terminated SiC surface, van der Waals-bonded honeycomb X-ene/graphene bilayers on top of the C-terminated SiC substrate are stable. Folded band structures show Dirac cones of the overlayers with small gaps of about 0.1 eV in between. The topological invariants of the peeled-off X-ene/graphene bilayers indicate the presence of topological character and the existence of a quantum spin Hall phase.